Work, values, and exercise : the impact of work on value priorities and exercise motivation - Heng, Jack (2018)
Observing the effect of working life on exercise motivation requires insight to the change in value priorities, based on Schwartz’s Value Theory (Schwartz, 1992). This qualitative study consists of interviewing six teachers from different Singapore Primary Schools with the aim of understanding their values and their exercise motivation before and after the transition to work. The results show that exercise or sport participation had mostly dropped in frequency and regularity because of work. This can be attributed to the season in life at which the participants were in, which prompted a change in value priorities, and consequently exercise motivation. The interviews employed several questions to gather data relating to the participant’s motivations, perception of exercise and sport, priorities in life, and their experiences with regards to exercise participation before and after they had begun work. Utilizing these responses, it was concluded that the participants had elevated the motivational goals of values belonging to the domain of self-transcendence and conservation. Due to the increased importance placed on such values, behaviors to achieve a correspondence to these values did not involve much of sports or exercise but rather other methods in spending time with people and the like. The participation of exercise and sport did not help the participants in the fulfillment of the motivational emphases of their prioritized values and were somewhat neglected. Future studies could include a more comprehensive research into work’s effect on value priorities and exercise motivation by including a larger sample size and other vocations besides teachers.